INTELLECTUAL WELLNESS: A COMPARISON OF PUBLIC AND PRIVATE MEDICAL UNIVERSITY TEACHERS - Syed, Sadiqa; Rehman, Rehana; Hussain, Mehwish; Shaikh, Saif Ullah (Pakistan Journal of Physiology, 2016)
Background: Educational leaders make their best efforts to enhance their scholastic skills while acquiring healthy learning, critical feedback and analytic mindfulness. There are a number of triggering factors influencing intellectual wellness (IW) of a teacher in a developing country like Pakistan. We aimed to observe IW awareness on the basis of type of university and income through salary and duration of employment in teachers of basic sciences at medical universities of Karachi, Pakistan. Methods: The survey was carried out in 3 public and 5 private medical universities of Karachi, Pakistan from January 2012 till December 2014. Questionnaire was tailored from â€œWellness Wheelâ€ and responses were collected on eight items in the dimension of IW in 4-points Likert scale as 1: never, 2: sometimes, 3: usually and 4: always. Individual responses were accumulated for IW score which were described as mean with standard deviation. The composite score was compared by Mann-Whitney U test for factors like type of institute and Kruskal Wallis test for factors having more than two categories like income and duration of employment. Results: Response was acquired from 261/300 faculty members making a response rate of 87%. Teachers from private medical university were well versed in conventional and problem based learning (p<0.0001). Involvement in research projects got intensified with enhancement of income through salary (p=0.0001). Duration of employment increased the likelihood of adding variety in teaching (p=0.003), adopt changes (p=0.05) and accepting healthy criticism (p=0.05). Conclusion: Pragmatic awareness of IW of medical teachers was significantly better in private medical universities with a higher pay package, reasonable work load, better occupational environment and with progression of experience. Pak J Physiol 2016;12(4):16â€“20